A comprehensive method to study the DNA's association with lamin and chromatin compaction in intact cell nuclei at super resolution. Issue 2 (16th December 2022) - Chapman, Katarina B.; Filipsky, Filip; Peschke, Nicolas; Gelléri, Márton; Weinhardt, Venera; Braun, Andrejs; Hausmann, Michael; Cremer, Christoph
Abstract : We expanded the fBALM (DNA structure fluctuation-assisted binding activated localization microscopy) method by developing a stable methodological sequence that enables dual-color imaging of high-resolution genomic DNA together with LaminB1. Abstract : Super-resolution fluorescence microscopy has revolutionized multicolor imaging of nuclear structures due to the combination of high labeling specificity and high resolution. Here we expanded the recently developed fBALM (DNA structure fluctuation-assisted binding activated localization microscopy) method by developing a stable methodological sequence that enables dual-color imaging of high-resolution genomic DNA together with an immunofluorescently labeled intranuclear protein. Our measurements of the nuclear periphery, imaging DNA and LaminB1 in biologically relevant samples, show that this novel dual-color imaging method is feasible for further quantitative evaluations. We were able to study the relative spatial signal organization between DNA and LaminB1 by means of highly specific colocalization measurements at nanometer resolution. Measurements were performed with and without the antifade embedding medium ProLong Gold, which proved to be essential for imaging of LaminB1, but not for imaging of SytoxOrange labeled DNA. The localization precision was used to differentiate between localizations with higher and lower amounts of emitting photons. We interpret high intensity localizations to be renatured DNA sections in which a high amount of Sytox Orange molecules were bound. This could give insight into the denaturation kinetics of DNA during fBALM. These results were further complemented by measurements of γH2AX and H3K9me3 signal organization to demonstrate differences within the chromatin landscape, which were quantified with image processing methods such as Voronoi segmentation.